Microbial-induced calcium carbonate precipitation: Influencing factors, nucleation pathways, and application in waste water remediation - Liu, Yu; Ali, Amjad; Su, Jun-Feng; Li, Kai; Hu, Rui-Zhu; Wang, Zhao (The Science of the total environment, 2023)
Microbial-induced calcium carbonate precipitation (MICP) is a technique that uses the metabolic action of microorganisms to produce CO32− which combines with free Ca2+ to form CaCO3 precipitation. It has gained widespread attention in water treatment, aimed with the advantages of simultaneous removal of multiple pollutants, environmental protection, and ecological sustainability. This article reviewed the mechanism of MICP at both intra- and extra-cellular levels. It summarized the parameters affecting the MICP process in terms of bacterial concentration, ambient temperature, etc. The current status of MICP application in practical engineering is discussed. Based on this, the current technical difficulties faced in the use of MICP technology were outlined, and future research directions for MICP technology were highlighted. This review helps to improve the design of existing water treatment facilities for the simultaneous removal of multiple pollutants using the MICP and provides theoretical reference and innovative thinking for related research. [Display omitted] •Microbially induced calcium precipitation was reviewed in the water treatment.•The mechanism of MICP is explained through both intra- and extracellular aspects.•The effect of environmental conditions on MICP is discussed.•The process applications of MICP in water treatment are discussed.•The limitations of MICP and future research directions are highlighted.